2006
DOI: 10.1088/0022-3727/39/4/019
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of exchange bias in Ir–Mn/Co0.9Fe0.1bilayers by inserting an ultra-thin Co0.6Fe0.4layer

Abstract: The exchange biasing of Co0.9Fe0.1 film by the antiferromagnet Ir–Mn via a thin intermediate Co0.6Fe0.4 layer was investigated. It has been found that the exchange bias is drastically enhanced with the insertion of an ultra-thin Co0.6Fe0.4 layer at the interface between Co0.9Fe0.1 and Ir–Mn layers. For the Ir0.25Mn0.75(100 Å)/Co0.9Fe0.1(150 Å) bilayer, the pinning field at room temperature is raised from 92 to 206 Oe when a 4 Å Co0.6Fe0.4 layer is introduced at the interface, and further enhanced to 262 Oe wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As is known, the exchange bias of IrMn/Co 100−x Fe x bilayers with the in-plane anisotropy strongly depends on the Co-Fe composition, and the maximum unidirectional anisotropy is at x = 30-40 [12]. It has been further demonstrated that the in-plane exchange bias of IrMn/Co 90 Fe 10 bilayers is tripled with the insertion of a thin Co 60 Fe 40 0022-3727/09/115002+05$30.00 layer at the interface [13]. In this paper, we systematically investigated the PEB of the bottom pinned IrMn/[(Co/Pt) 3 ] and IrMn/Co 60 Fe 40 /[(Pt/Co) 2 ] multilayer films, and found a further twofold enlargement of the PEB in the optimized IrMn/[Co/Pt] multilayer when a thin Co 60 Fe 40 layer replaces the Co layer adjacent to IrMn.…”
Section: Introductionmentioning
confidence: 97%
“…As is known, the exchange bias of IrMn/Co 100−x Fe x bilayers with the in-plane anisotropy strongly depends on the Co-Fe composition, and the maximum unidirectional anisotropy is at x = 30-40 [12]. It has been further demonstrated that the in-plane exchange bias of IrMn/Co 90 Fe 10 bilayers is tripled with the insertion of a thin Co 60 Fe 40 0022-3727/09/115002+05$30.00 layer at the interface [13]. In this paper, we systematically investigated the PEB of the bottom pinned IrMn/[(Co/Pt) 3 ] and IrMn/Co 60 Fe 40 /[(Pt/Co) 2 ] multilayer films, and found a further twofold enlargement of the PEB in the optimized IrMn/[Co/Pt] multilayer when a thin Co 60 Fe 40 layer replaces the Co layer adjacent to IrMn.…”
Section: Introductionmentioning
confidence: 97%
“…Magnetic CoFeB, Co, or NiFe thin film can be inserted as a free and/or pinned layer into the MTJ device, as it has a high spin tunneling efficiency and its spin-valve structure exhibits ferromagnetism (FM)/antiferromagnetism (AFM) exchange-biasing anisotropy [7][8][9][10]. Moreover, the favorable characteristics of the MTJ device, including high tunneling magnetoresistance (TMR), strength, and durability, are critical to operation of an MTJ device at room temperature (RT) and in high-temperature environments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…To clearly separate different physical mechanisms of magnetic damping in spin valves, we have studied the magnetic damping in the exchange-biased spin valve IrMn/CoFe/Cu/CoFeB. Benefitting from the large exchange-biased field (∼560 Oe) between IrMn and CoFe [26], we have convincingly revealed the magnetic dynamical property variation of the free CoFeB layer in various magnetic configurations with a sufficient field window for each configuration. We have observed that the CoFeB layer damping constant varies very little between the parallel and antiparallel configurations, but in the intermediate states of the pinned CoFe layer during its magnetization reversal, where multi-domains in the CoFe layer are confirmed, the damping constant exhibits significant enhancement together with a small resonance frequency shift.…”
Section: Introductionmentioning
confidence: 94%